2022
DOI: 10.1002/jmv.27824
|View full text |Cite
|
Sign up to set email alerts
|

Pulse versus nonpulse steroid regimens in patients with coronavirus disease 2019: A systematic review and meta‐analysis

Abstract: Systemic steroids are associated with reduced mortality in hypoxic patients with coronavirus disease 2019 (COVID-19). However, there is no consensus on the doses of steroid therapy in these patients. Several studies showed that pulse dose steroids (PDS) could reduce the progression of COVID-19 pneumonia. However, data regarding the role of PDS in COVID-19 is still unclear. Therefore, we performed this meta-analysis to evaluate the role of PDS in COVID-19 patients compared to nonpulse steroids (NPDS). Comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
(119 reference statements)
1
1
0
Order By: Relevance
“…Indeed, regardless of steroid dose, there was no improvement among iMV-free patients. Similar to our results, prior studies reported that appropriate selection of patients to be treated with high-dose methylprednisolone is necessary to optimise the riskbenefit balance of steroids for acute COVID-19 patients [7,[25][26][27][28].…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, regardless of steroid dose, there was no improvement among iMV-free patients. Similar to our results, prior studies reported that appropriate selection of patients to be treated with high-dose methylprednisolone is necessary to optimise the riskbenefit balance of steroids for acute COVID-19 patients [7,[25][26][27][28].…”
Section: Discussionsupporting
confidence: 89%
“…Although corticosteroid therapy was administered to pre-ICU patients a median of six days from symptom onset at an oxygen saturation-to-fraction of inspiratory oxygen ratio of 404.2 (equivalent to an oxygen saturation of 85% while the patient was breathing ambient air at rest), it did not prevent ICU admission in this study. A meta-analysis reported that, compared to non-pulse dose steroids, pulse dose steroids are associated with a similar mortality rate and need for endotracheal intubation ( 17 ). Recently, a randomized control trial reported that no significant differences between pulse methylprednisolone and placebo arms were observed for admission to the ICU with orotracheal intubation or death ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, many centres, particularly in India and other Asian countries, started using higher doses including pulse dose of steroids for almost all hospitalised patients whether hypoxaemic or non-hypoxaemic that could be an underlying cause of increased mortality in the disease. [ 3 ]…”
mentioning
confidence: 99%